HUKUM SEBAGAI ALAT REKAYASA SOSIAL DALAM PRAKTEK BERHUKUM DI INDONESIA - H.Yacob Djasmani (Masalah-Masalah Hukum, 2011)
Law as tool of social engineering cannot be provided in Indonesia. It is because on the government perspective, law be regarded just a rule or act or legal, produced by legislation process. Law is used to support the government in the development process. Based on this perspective, law making is less from the pluralism society value. The positivism perspective is used in law making (deductive frame think) based on civil law system tradition. Law as tool of social engineering would be effective, if law making process give notice the customary law developing in society, caused its have arrangement capability to society. The government ,so that is way, must give space customary law to grow and be integrated as a part of national legal system.